Rapid CRISPR/Cas9 Editing of Genotype IX African Swine Fever Virus Circulating in Eastern and Central Africa - Abkallo, Hussein M.; Svitek, Nicholas; Oduor, Bernard; Awino, Elias; Henson, Sonal P.; Oyola, Samuel O.; Mwalimu, Stephen; Assad-Garcia, Nacrya; Fuchs, Walter; Vashee, Sanjay; Steinaa, Lucilla (Frontiers in Genetics, 2021)
African swine fever virus (ASFV) is the etiological agent of a contagious and fatal disease of domestic pigs that has significant economic consequences for the global swine industry. Due to the lack of effective treatment and vaccines against African swine fever, there is an urgent need to leverage cutting-edge technologies and cost-effective approaches for generating and purifying recombinant virus to fast-track the development of live-attenuated ASFV vaccines. Here, we describe the use of the CRISPR/Cas9 gene editing and a cost-effective cloning system to produce recombinant ASFVs. Combining these approaches, we developed a recombinant virus lacking the non-essential gene A238L (5EL) in the highly virulent genotype IX ASFV (ASFV-Kenya-IX-1033) genome in less than two months as opposed to the standard homologous recombination with conventional purification techniques which takes up to six months on average. Our approach could therefore be a method of choice for less resourced laboratories in developing nations.